The East Asian Challenge for Democracy : Political Meritocracy in Comparative Perspective - Bell, Daniel A.; Li, Chenyang (Cambridge : Cambridge University Press, 2013)
The rise of China, along with problems of governance in democratic countries, has reinvigorated the theory of political meritocracy. But what is the theory of political meritocracy and how can it set standards for evaluating political progress (and regress)? To help answer these questions, this volume gathers a series of commissioned research papers from an interdisciplinary group of leading philosophers, historians and social scientists. The result is the first book in decades to examine the rise (or revival) of political meritocracy and what it will mean for political developments in China and the rest of the world. Despite its limitations, meritocracy has contributed much to human flourishing in East Asia and beyond and will continue to do so in the future. This book is essential reading for those who wish to further the debate and perhaps even help to implement desirable forms of political change.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).